2004
DOI: 10.1111/j.1462-5822.2004.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated mortality in immune challenged mosquitoes (Aedes aegypti) correlates with a decrease in haemocyte numbers

Abstract: SummaryMosquitoes vector pathogens. One aspect that has been overlooked in mosquito-pathogen relationships is the effect of host age on immune competence. Here, we show that there is age-associated mortality following immune challenge with Escherichia coli . This mortality correlates with a decrease in haemocyte numbers (blood cells) and a decreased ability to kill E. coli . Although the number of haemocytes decreases, the available haemocytes retain their phagocytic ability regardless of age, and we estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
140
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(146 citation statements)
references
References 50 publications
4
140
2
Order By: Relevance
“…However, the increase observed here contrasts with other studies showing a decrease in THC (Hillyer et al 2005;Cornet et al 2009) and still others showing an initial decrease followed by a return to prior levels (Persson et al 1987;Lorenzon et al 1999). This discrepancy can be attributed to a number of possible factors.…”
Section: Variability Of Immune Response Among Clonescontrasting
confidence: 99%
“…However, the increase observed here contrasts with other studies showing a decrease in THC (Hillyer et al 2005;Cornet et al 2009) and still others showing an initial decrease followed by a return to prior levels (Persson et al 1987;Lorenzon et al 1999). This discrepancy can be attributed to a number of possible factors.…”
Section: Variability Of Immune Response Among Clonescontrasting
confidence: 99%
“…Nevertheless, hemocyte loss in adult honeybees might be regulated by endocrine factors. Age-related hemocyte loss has been recorded in other insect species (Hillyer et al, 2005;Stanley and Park, unpublished data). For one example, Stanley and Park (unpublished data) recorded a steady decline in hemocyte populations in adult males of the cricket Gryllus firmus beginning after they reached the age of 3 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In scorpion flies (Panorpa vulgaris), whilst haemocyte numbers remained unchanged during ageing, the phagocytic activity of those cells declined [23]. Hillyer et al, [24] showed that older mosquitoes (Aedes aegypti) had reduced survival following infection with E. coli, a lower ability to clear the infection, and [5] fewer phagocytic haemocytes compared with younger mosquitoes. However they only assayed mosquitoes across the first five days of life, so it is questionable whether these trends truly represent senescence or some other life-history shift.…”
Section: Introductionmentioning
confidence: 99%